Penggunaan Tablet di Binus Online Learning - Agus Putranto; Wawan Saputra (Bina Nusantara University, 2014)
Utilization of e-learning can improve learning effectiveness and flexibility. Features of e-learning that are important in teaching and learning activities are tasks features, discussion forums and discussion face to face in a video conference. BINUS Online Learning is a program that offers students to conduct online lectures. Online BINUS need to think about software and hardware that must be provided in a tablet. Therefore, this study will analyze the use of the tablet which will be used for student BINUS Online Learning. The purpose of this study is to analyze the needs, and then determines the specifications of the tablet to be used as a replacement for netbook facility at Binus Online Learning. The research methodology used include, among others: Data Collection Methods (by conducting surveys), and the analysis method that consists of literature study and analysis of the system running, by using the rich picturer.